Compact high-gain circularly polarized patch antenna based on TM30/TM03 mode - Hoang Nguyen-Huy; Duc-Nguyen Tran-Viet; Phuong Kim-Thi; Hung Tran-Huy (PLoS ONE, 2025)
This paper presents a circularly polarized (CP) microstrip patch antenna with high gain and compact size characteristics. For high gain radiation, the principle is to employ high-order mode patch. By using diagonal feed and unequal center crossed slot, two orthogonal modes including TM03 and TM30 modes are generated with equal magnitude and 90∘ phase difference. Thus, the high-order mode patch antenna can radiate CP waves with high gain. To achieve small lateral dimensions with low back radiation, the patch is surrounded by a substrate integrated waveguide (SIW) cavity. For validation, measurement is implemented on an antenna prototype. The final design has overall dimensions of 1.27λ × 1.27λ × 0.03λ at the center operating frequency. The measured operating bandwidth, in which reflection coefficient and axial ratio are respectively less than –10 dB and 3 dB, is from 5.435 to 5.475 GHz. Within this band, the antenna exhibits high gain radiation of about 12 dBi. Besides, compared to the antenna without SIW cavity, the back radiation of the proposed design can be decreased by two times.